2006
DOI: 10.1038/ni1394
|View full text |Cite|
|
Sign up to set email alerts
|

T cell anergy is reversed by active Ras and is regulated by diacylglycerol kinase-α

Abstract: T cell anergy has been correlated with defective signaling by the GTPase Ras, but causal and mechanistic data linking defective Ras activity with T cell anergy are lacking. Here we used adenoviral transduction to genetically manipulate nonproliferating T cells and show that active Ras restored interleukin 2 production and mitogen-activated protein kinase signaling in T cells that were made anergic in vitro or in vivo. Diacylglycerol kinases (DGKs), which negatively regulate Ras activity, were upregulated in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
271
3
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(287 citation statements)
references
References 42 publications
9
271
3
2
Order By: Relevance
“…Two independent investigators have observed that diacylglycerol kinase-α (DGK-α) is upregulated in anergic T cells [65,66], indicating that there is a link between the TCR signaling molecule DAG and T cell responsiveness. As depicted in Fig.…”
Section: Role Of Signaling Molecules In T Cell Hyporesponsivenessmentioning
confidence: 99%
“…Two independent investigators have observed that diacylglycerol kinase-α (DGK-α) is upregulated in anergic T cells [65,66], indicating that there is a link between the TCR signaling molecule DAG and T cell responsiveness. As depicted in Fig.…”
Section: Role Of Signaling Molecules In T Cell Hyporesponsivenessmentioning
confidence: 99%
“…The ERK kinases overcome SHP-1 phosphatase blockade of proximal T cell receptor (TCR) signaling (5), and more globally, influence the maturation of T cells in the thymus (6 -9) and production of interleukin-2 (IL-2) in the post-thymic peripheral T cells (10 -14). The observation that a relative lack of Ras/ERK signal is associated with inability of T cells to respond to an antigen further underscores the fundamental role of this signaling pathway in T cell stimulation (15)(16)(17). It is not surprising to find therefore that T cells and other cell types have developed inhibitors to control the magnitude and duration of the ERK signaling.…”
mentioning
confidence: 99%
“…Ras and Erk1/2 have been implicated in both positive selection and negative selection (12-17). Recent evidence indicates that DGK␣ and , isoforms known to be expressed in T cells negatively control DAG and the Ras-Erk1/2 signaling pathway after TCR engagement (18)(19)(20)(21)(22). Deficiency of either DGK␣ or causes enhanced T cell activation and resistance to anergy induction (19,20).…”
mentioning
confidence: 99%